Comparison of Clinical Results in Nasal Tip Augmentation Either Via Face to Face or Back to Back Technique With Autogenous Auricular Conchal Cartilage. Issue 7 (October 2015) - Sahin, Murat Sertan; Kasapoglu, Fikret; Demir, Uygar Levent; Ozmen, Omer Afsin; Coskun, Hakan; Basut, Oguz
Abstract : Objective: To compare the objective and subjective findings between patients who underwent nasal tip augmentation surgery via two different methods using autogenous auricular conchal cartilage. Materials and Methods: This study included the data of 21 patients who underwent nasal tip augmentation surgery. The patients were randomly divided in two groups according to the technique used to form a double layer columellar strut graft; either face to face (group 1) and back to back (group 2). All patients were assessed via nasal obstruction symptom evaluation scale (NOSE) and via acoustic rhinometry and rhinomanometry at preoperative and postoperative 1st and 6th months. Results: There was statistically significant improvement in symptom score in both patient groups with no difference inbetween. Total nasal resistance decreased nonsignificantly at the end of 6th month in both groups; 13.1 Pa/cm 3 to 8.6 Pa/cm 3 and 10.3 Pa/cm 3 to 9.5 Pa/cm 3 respectively. There was no significant increment in MCA values for both groups except left MCA1. Conclusions: We achieved good results in tip augmentation via both techniques. An autogenous conchal cartilage is a good alternative to replace lacking caudal septal cartilage. It provides safe and stable support to the nasal tip. However, further comprehensive studies with larger sample size and long follow-up are required to elucidate any difference between these two techniques.